EVALUASI METODE DEMONSTRASI DALAM PENYAMPAIAN PESAN KEPADA PENGRAJIN BAMBU DI DUSUN NGLISENG, MUNTUK, DLINGO - Indardi (LP3 UMY, 2015)
Its sims are : u To know the effectiveness method of yield and manner demonstralion to increase the crafsmen's btowledge. b. To know the effecliveness method of yield and manner demonstration to change the craftsmen's auitude. c, To know lhe eflectiyeness method of yield and manner demonslration to increase the skills, and the general aim is to know lhe efectiveness mehod oJyield and manner demonstration in the mes s age ff ansforms t i on.